Zerumbone-loaded nanostructured lipid carriers: preparation, characterization, and antileukemic effect - Rahman, Heshu Sulaiman; Abdullah, Rasedee; How, Chee Wun; Abdul, Ahmad Bustamam; Allaudin, Zeenathul Nazariah; Othman, Hemn Hassan; Saeed, Mohamed Ibrahim; Yeap, Swee Keong (Dove Medical Press, 2013)
Zerumbone, a natural dietary lipophilic compound with low water solubility (1.296 mg/L at 25°C) was used in this investigation. The zerumbone was loaded into nanostructured lipid carriers using a hot, high-pressure homogenization technique. The physicochemical properties of the zerumbone-loaded nanostructured lipid carriers (ZER-NLC) were determined. The ZER-NLC particles had an average size of 52.68 ± 0.1 nm and a polydispersity index of 0.29 ± 0.004 μm. Transmission electron microscopy showed that the particles were spherical in shape. The zeta potential of the ZER-NLC was −25.03 ± 1.24 mV, entrapment efficiency was 99.03%, and drug loading was 7.92%. In vitro drug release of zerumbone from ZER-NLC was 46.7%, and for a pure zerumbone dispersion was 90.5% over 48 hours, following a zero equation. Using the MTT (3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) assay in human T-cell acute lymphoblastic leukemia (Jurkat) cells, the half maximal inhibitory concentration (IC50) of ZER-NLC was 5.64 ± 0.38 μg/mL, and for free zerumbone was 5.39 ± 0.43 μg/mL after 72 hours of treatment. This study strongly suggests that ZER-NLC have potential as a sustained-release drug carrier system for the treatment of leukemia.